(untitled) (JOURNAL OF ADVANCES IN AGRICULTURE, 2018)
The demographic development of human population, the pollution, with pesticides, the needs for better quality crops, determined the farmers, policy makers, scientists and the public to make steps further in order to adopt strategies, to issue laws, guides, directives to implement in practice the use of IPM and biological control of pests and Phyto-pathogens for implementing sano-genetic advanced agriculture. This is a short review paper discussing the modern and future IPM.